Sovereign debt sustainability and private sector credit in Kenya - Odongo Kodongo (Kenya Bankers Association (KBA), 2025)
ypical debt sustainability metrics characterize Kenya's sovereign debt as "unsustainable" since around 2019. Further, the data show that, over time, commercial banks' private sector lending has declined while lending to the government has grown. Given these observations, this study examines whether sovereign debt has a discernible relationship with private sector credit growth and documents a characteristic negative relationship between sovereign debt and private credit growth; the negative relationship is stronger during periods when sovereign debt is arguably unsustainable. Informed by this finding, the study tests for the possible moderating influence of financial conditions on the established empirical relationship. Financial conditions have worsened considerably since around 2013 when our construct turns positive, or "restrictive". The tests show that financial conditions have a significant adverse moderating effect on the relationship between (domestic) sovereign debt and private sector credit growth. Informed by these findings, the study also tests for the possible existence of a threshold level of sovereign debt at which the negative relationship between sovereign debt and credit growth worsens: the results are inconclusive. Guided by these findings, the paper proffers several policy recommendations.
Keywords: 330; Public debt; Debt management; Lending; Private sector; Kenya; Öffentliche Schulden; Schuldenmanagement; Kreditgeschäft; Privatwirtschaft; Kenia